A sympathy with sounds: Ray Bradbury and BBC Radio, 19511970. (17th October 2007) - Nichols, Phil
The American writer Ray Bradbury has a long association with BBC radio. His works have been dramatised many times, often by others, but occasionally by himself. Drawing on research in the BBC Written Archives, this paper gives an account of Bradbury's treatment by the BBC, focusing on the period 19511970, and shows how a key work (the little known Leviathan '99) unites much of Bradbury's canon.